2013
DOI: 10.1186/1471-2105-14-362
|View full text |Cite
|
Sign up to set email alerts
|

iMir: An integrated pipeline for high-throughput analysis of small non-coding RNA data obtained by smallRNA-Seq

Abstract: BackgroundQualitative and quantitative analysis of small non-coding RNAs by next generation sequencing (smallRNA-Seq) represents a novel technology increasingly used to investigate with high sensitivity and specificity RNA population comprising microRNAs and other regulatory small transcripts. Analysis of smallRNA-Seq data to gather biologically relevant information, i.e. detection and differential expression analysis of known and novel non-coding RNAs, target prediction, etc., requires implementation of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…Interestingly, around 0.5% of Rfam reads aligned to known piRNA sequences annotated in piRNA Bank, 33 which is in line with recent findings demonstrating piRNA expression and activity in other somatic tissues. [20][21][22][23] Sequencing revealed significant differences in miRNA expression patterns between BSM cells of asthmatic patients and healthy subjects and demonstrated for the first time that piRNAs are also expressed in airway BSM cells, showing differential expression between the 2 conditions. In total, we identified that the expression of 32 sncRNAs (26 known miRNAs, 5 piRNAs, and 1 snoRNA) demonstrates statistically significant differential expression (jFCj > _ 1.3, P < .05) in BSM cells of asthmatic patients with respect to those from healthy subjects (Table I).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, around 0.5% of Rfam reads aligned to known piRNA sequences annotated in piRNA Bank, 33 which is in line with recent findings demonstrating piRNA expression and activity in other somatic tissues. [20][21][22][23] Sequencing revealed significant differences in miRNA expression patterns between BSM cells of asthmatic patients and healthy subjects and demonstrated for the first time that piRNAs are also expressed in airway BSM cells, showing differential expression between the 2 conditions. In total, we identified that the expression of 32 sncRNAs (26 known miRNAs, 5 piRNAs, and 1 snoRNA) demonstrates statistically significant differential expression (jFCj > _ 1.3, P < .05) in BSM cells of asthmatic patients with respect to those from healthy subjects (Table I).…”
Section: Discussionmentioning
confidence: 97%
“…Using iMir software, 23 we identified 11 novel miRNAs: 7 by using miRanalyzer and 4 by using miRDeep2 algorithms (see Tables E3 and E4 in this article's Online Repository at www.jacionline.org). Only miRNA candidates expressed with 30 or more read counts in at least 3 samples were considered true novel miRNAs (see Table E5 in this article's Online Repository at www.jacionline.org).…”
Section: Novel Mirna Candidate Identification In Bsm Cellsmentioning
confidence: 99%
“…The data obtained from the sequencer were analyzed using iMir, a modular pipeline for comprehensive analysis of small RNA-Seq data, comprising specific tools for adapter trimming, quality filtering, identification of known sncRNAs, novel miRNA prediction, differential expression analysis and target prediction [72, 73]. …”
Section: Methodsmentioning
confidence: 99%
“…Sequence reads were then filtered for quality and clustered to unique sequences to remove redundancy, retaining their individual read count information. Unique sequences 18 nucleotides or more in length were mapped, without any mismatch, on miRNA annotation according to miRBase version 18 using iMir, a modular pipeline for comprehensive analysis of small RNA sequencing data, comprising specific tools for adapter trimming, quality filtering, identification of known small noncoding RNAs, novel miRNA prediction, differential expression analysis, and target prediction (37). The pipeline created has proven to be efficient and flexible enough to allow a user to select the preferred combination of analytical steps.…”
Section: Methodsmentioning
confidence: 99%